Syntheses and determination of absolute configurations and biological activities of the enantiomers of the longtailed mealybug pheromone - Ramesh, Remya; Swaroop, Pandrangi Siva; Gonnade, Rajesh G.; Thirupath, Choppari; Waterworth, Rebeccah A.; Millar, Jocelyn G.; Reddy, D. Srinivasa (Journal of Organic Chemistry, 2013)
Preparation and assignment of absolute configurations to both enantiomers of the sex pheromone of the longtailed mealybug, an irregular monoterpenoid with extraordinary biological activity, has been completed. Comparison of the biological activities of both enantiomers and the racemate in field trials showed that the (S)-(+)-enantiomer was highly attractive to male mealybugs, strongly suggesting that female longtailed mealybugs produce this enantiomer. The (R)-(-)-enantiomer was benign, being neither attractive nor inhibitory.

Zinc mediated allylations of chlorosilanes promoted by ultrasound: synthesis of novel constrained sila amino acids - Ramesh, Remya; Reddy, D. Srinivasa (Organic & Biomolecular Chemistry, 2014)
A simple, fast and efficient method for allylation and propargylation of chlorosilanes through zinc mediation and ultrasound promotion is reported. As a direct application of the resulting bis-allylsilanes, three novel, constrained sila amino acids are prepared for the first time. The design and synthesis of the constrained sila analogue of GABA (gamma-amino butyric acid) is a highlight of this work.

Design, synthesis, and identification of silicon incorporated oxazolidinone antibiotics with improved brain exposure - Seetharamsingh, B.; Ramesh, Remya; Dange, Santoshkumar S.; Khairnar, Pankaj V.; Singhal, Smita; Upadhyay, Dilip; Veeraraghavan, Sridhar; Viswanadha, Srikant; Vakkalanka, Swaroop; Reddy, D. Srinivasa (ACS Medicinal Chemistry Letters, 2015)
Therapeutic options for brain infections caused by pathogens with a reduced sensitivity to drugs are limited. Recent reports on the potential use of linezolid in treating brain infections prompted us to design novel compounds around this scaffold. Herein, we describe the design and synthesis of various oxazolidinone antibiotics with the incorporation of silicon. Our findings in preclinical species suggest that silicon incorporation is highly useful in improving brain exposures. Interestingly, three compounds from this series demonstrated up to a 30-fold higher brain/plasma ratio when compared to linezolid thereby indicating their therapeutic potential in brain associated disorders.
Keywords: Antibacterial; brain exposure; linezolid; oxazolidinone; sila analogue

Enantiospecific synthesis of both enantiomers of the longtailed mealybug pheromone and their evaluation in a new zealand vineyard - Ramesh, Remya; Bell, Vaughn; Twidle, Andrew M.; Gonnade, Rajesh G.; Reddy, D. Srinivasa (Journal of Organic Chemistry, 2015)
The irregular monoterpenoid sex pheromone of Pseudococcus longispinus and its enantiomer were prepared from the corresponding bornyl acetates. The use of readily accessible chiral starting materials and lactone lactone rearrangement are the highlights of the present synthesis. The biological activities of the two enantiomers and racemic mixture were tested in a New Zealand vineyard. The (S)-(+)-enantiomer was significantly more attractive to P. longispinus males than the racemic mixture or the (R)-(-)-enantiomer.

Silicon incorporated morpholine antifungals: design, synthesis, and biological evaluation - Jachak, Gorakhnath R.; Ramesh, Remya; Sant, Duhita G.; Jorwekar, Shweta U.; Jadhav, Manjusha R.; Tupe, Santosh G.; Deshpande, Mukund V.; Reddy, D. Srinivasa (ACS Medicinal Chemistry Letters, 2015)
Known morpholine class antifungals (fenpropimorph, fenpropidin, and amorolfine) were synthetically modified through silicon incorporation to have 15 sila-analogues. Twelve sila-analogues exhibited potent antifungal activity against different human fungal pathogens such as Candida albicans, Candida glabrata, Candida tropicalis, Cryptococcus neoformans, and Aspergillus niger. Si la-analogue 24 (fenpropimorph analogue) was the best in our hands, which showed superior fungicidal potential than fenpropidin, fenpropimorph, and amorolfine. The mode of action of sila-analogues was similar to morpholines, i.e., inhibition of sterol reductase and sterol isomerase enzymes of ergosterol synthesis pathway.
Keywords: Antifungal drugs; Candida albicans; ergosterol biosynthesis; morpholines; sila-analogues

Repurposing of a drug scaffold: identification of novel sila analogues of rimonabant as potent antitubercular agents - Ramesh, Remya; Shingare, Rahul D.; Kumar, Vinod; Anand, Amitesh; Swetha, B.; Veeraraghavan, Sridhar; Viswanadha, Srikant; Ummanni, Ramesh; Gokhale, Rajesh S.; Reddy, D. Srinivasa (European Journal of Medicinal Chemistry, 2016)
The structural similarity between an MmpL3 inhibitor BM212, and a cannabinoid receptor modulator rimonabant, prompted us to investigate the anti-tubercular activity of rimonabant and its analogues. Further optimization, particularly through incorporation of silicon into the scaffold, resulted in new compounds with significant improvement in anti-tubercular activity against Mycobacterium tuberculosis (H37Rv). The sila analogue 18a was found to be the most potent antimycobacterial compound (MIC, 31 ng/mL) from this series with an excellent selectivity index. (C) 2016 Elsevier Masson SAS. All rights reserved.

Quest for novel chemical entities through incorporation of silicon in drug scaffolds - Ramesh, Remya; Reddy, D. Srinivasa (Journal of Medicinal Chemistry, 2018)
In order to optimize a lead molecule for further development, bioisosteric replacements are generally adopted as one of the strategies. Silicon appears to be the right choice as a carbon isostere because of the similarity in chemical properties. Silicon can be strategically introduced in a molecule to modulate its druglike properties, providing medicinal chemists with an unconventional strategy for replacing a carbon atom. Silicon can also be introduced to replace other heteroatoms and can act as a surrogate of functional groups such as olefin and amide as well. The present Perspective focuses on the opportunities that silicon incorporation offers in drug discovery, with an emphasis on case studies where introduction of silicon has created a benefit over its analog. We have tried to highlight all the recent developments in the field and briefly discuss the challenges associated with them.

Identification of a novel series of potent organosilicon mosquito repellents - Kulkarni, Akshay S.; Ramesh, Remya; Walia, Safal; Sayyad, Shahebaz I.; Gathalkar, Ganesh B.; Balamkundu, Seetharamsing; Joshi, Manali; Sen, Avalokiteswar; Reddy, D. Srinivasa (ACS Omega, 2021)
Mosquito control by personal protection is one of the most efficient ways of curtailing deadly diseases such as malaria and dengue with the potential to save millions of lives per year. DEET (N,N-diethyl-3-methyl benzamide) is currently considered as the gold standard for mosquito repellents, being used for the past several decades. Control by DEET, however, is being threatened by emerging resistance among mosquitoes. To address this concern and also to improve protection times, we synthesized a novel series of 25 silicon-containing acyl piperidines using acid–amine coupling protocol and tested their activity against Aedes aegypti in mosquito-repellent assays. Several compounds from this series appear to possess good mosquito-repellent properties. Most notably, at 0.5 mg/cm2 concentrations, the mean protection time for NDS100100 was 756 min, which was higher than that of DEET (616 min). The details of design, synthesis, and biological evaluation are discussed herein.

Developing a mealybug pheromone monitoring tool to enhance IPM practices in New Zealand vineyards - Sullivan, Nicola J.; Bell, Vaughn A.; Butler, Ruth C.; Wallis, Roger; Ramesh, Remya; Reddy, D. Srinivasa; Twidle, Andrew M.; Bunn, Barry; Unelius, C. Rikard; Manning, Lee-Anne M.; Suckling, David M. (Journal of Pest Science, 2023)
Mealybugs are phloem-feeding insects found on many crops worldwide. In New Zealand vineyards, they transmit the economically important Grapevine leafroll-associated virus 3 (GLRaV-3). For some mealybug species, synthetic sex pheromones have been commercialised, and are used as monitoring tools. The mealybugs Pseudococcus longispinus and Pseudococcus calceolariae are major pests in many New Zealand vineyards. We present work on the development of a combined P. longispinus and P. calceolariae pheromone lure. The optimal dose for monitoring P. longispinus was found to be 10 mu g of the (S)-(+)-enantiomer, either alone or in the racemic mixture. Addition of the corresponding alcohol did not improve trap catch of P. longispinus. Both the P. longispinus and the P. calceolariae pheromone lures remained active in the field for 90 days. Combining the 2 species' pheromones had no negative effects on male mealybug trap catch for either species. We conclude that the pheromone ester alone is the best lure for the male P. longispinus. Combining the two mealybug species' pheromones into a single lure provides the New Zealand viticultural industry with an efficient monitoring tool. Late-vintage deployment of baited lures will provide information on mealybug abundance and local distribution that will inform the scope of future insecticide programmes, to target areas based on need rather than an area-wide application by default.
Keywords: Citrophilus mealybug; Integrated pest management (IPM); Long-tailed mealybug; monitoring; Pseudococcus calceolariae; Pseudococcus longispinus

Synthesis, biological evaluation and docking studies of silicon incorporated diarylpyrroles as MmpL3 inhibitors: an effective strategy towards development of potent anti-tubercular agents - Vasudevan, N.; Motiwala, Zenia; Ramesh, Remya; Wagh, Sachin B.; Shingare, Rahul D.; Katte, Revansiddha; Anand, Amitesh; Choudhary, Sushil; Kumar, Ajay; Gokhale, Rajesh S.; Kulkarni, Kiran A.; Reddy, D. Srinivasa (European Journal of Medicinal Chemistry, 2023)
Growing global demand for new molecules to treat tuberculosis has created an urgent need to develop novel strategies to combat the menace. BM212 related compounds were found to be potent anti-TB agents and they inhibit mycolic acid transporter, MmpL3, a known potent drug target from Mycobacterium tuberculosis. In order to enhance their inhibitory potency, several silicon analogues of diarylpyrroles related to BM212 were designed, synthesized, and evaluated for anti-tubercular activities. In Alamar blue assay, most of the silicon-incorporated compounds were found to be more potent than the parent compound (BM212), against Mycobacterium tuberculosis (MIC = 1.7 & mu;M, H37Rv). Docking results from the crystal structure of MmpL3 and silicon analogues as pharmacophore model also strongly correlate with the biological assays and suggest that the incorporation of silicon in the inhibitor scaffold could enhance their potency by stabilizing the hydrophobic residues at the binding pocket. The best docking hit, compound 12 showed an MIC of 0.1 & mu;M against H37Rv with an acceptable in vitro ADME profile and excellent selectivity index. Overall, the present study indicates that, the designed silicon analogues, especially compound 12 could be a good inhibitor for an intrinsically flexible drug-binding pocket of MmpL3 and has potential for further development as anti-tubercular agents.
Keywords: antibiotic; BM212; docking studies; MmpL3 inhibitor; Silicon analogue; tuberculosis